2020
DOI: 10.1177/1559827620930962
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Remission and Lifestyle Medicine: A Position Statement From the American College of Lifestyle Medicine

Abstract: Objectives. The present review represents the position of the American College of Lifestyle Medicine on type 2 diabetes (T2D) and remission treatment. Background. Research now reveals that sufficiently intensive lifestyle interventions can produce remission of T2D with similar success to bariatric surgery, but with substantially fewer untoward side effects. Methods. A literature review was conducted to examine lifestyle modifications targeting T2D remission, with most studies using a combination of blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 88 publications
0
76
0
Order By: Relevance
“…Diabetes remission was always accompanied by weight loss as a symptomatic effect of the metabolic improvements. Kelly et al [77] reported a mean diabetes remission rate of 49.4 % applying very low calorie diets. The VLCD part of the intermittent hepatic therapy, which is focused on the cause of insulin resistance, delivers more effective results, as our reported data show (▶Fig.…”
Section: Personalized Molecular Nutrition For Type 2 Diabetes Remissionmentioning
confidence: 99%
“…Diabetes remission was always accompanied by weight loss as a symptomatic effect of the metabolic improvements. Kelly et al [77] reported a mean diabetes remission rate of 49.4 % applying very low calorie diets. The VLCD part of the intermittent hepatic therapy, which is focused on the cause of insulin resistance, delivers more effective results, as our reported data show (▶Fig.…”
Section: Personalized Molecular Nutrition For Type 2 Diabetes Remissionmentioning
confidence: 99%
“…At the tissue level, studies using magnetic resonance imaging have demonstrated lipid deposition in muscle and liver cells, leading to insulin resistance ( 52 ). Interventional trials using plant-based diets suggest that these diets can improve and potentially even reverse the course of diabetes ( 53 ).…”
Section: Lifestyle Medicine Domain-specific Findings and Recommendatimentioning
confidence: 99%
“…This discussion becomes even more pertinent, considering the fact that these glucose-lowering therapies are being exapted for use in non-glycemic indications such as obesity, heart failure and chronic kidney disease [12][13][14]. If calorie restriction can be accepted as a part of lifestyle medicine [1], while defining diabetes remission, the use of a calorie restriction mimetic should be accepted as well.…”
Section: Drug-sensitive Remissionmentioning
confidence: 99%
“…Diabetes remission is an often-discussed topic in contemporary endocrinology. A recent position statement suggests that the remission should be the primary clinical goal of diabetes management [ 1 ]. Whether this is possible or not for persons living with established type 2 diabetes, complicated type 2 diabetes, type 1 diabetes or pancreatic diabetes is a debate in itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation